2009
DOI: 10.1021/cg900873t
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Cocrystals Reported Prior to 2000

Abstract: A history of cocrystals reported in the literature prior to the year 2000 is presented. Concentration is on cocrystals that contain only organic components, not including species commonly referred to as solvates and clathrates. However, brief mention is made of some cocrystals containing both organic and inorganic components. The discovery and early history of cocrystals are discussed, with emphasis on centers of activity. Numerous examples are then utilized to illustrate the structural variety and utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
157
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(160 citation statements)
references
References 173 publications
2
157
0
1
Order By: Relevance
“…For example, preliminary results show that the molecular pores can be imbibed into various porous supports, such as cellulose filter paper, to introduce a degree of microporosity into otherwise macroporous materials. Our results also suggest the possibility of modular 'mix and match' strategies in which a number of different molecular pores are combined in a single-amorphous solid, each perhaps containing a different chemical functionality 39 , without satisfying the stringent requirements of co-crystallization 40 .…”
Section: Discussionmentioning
confidence: 88%
“…For example, preliminary results show that the molecular pores can be imbibed into various porous supports, such as cellulose filter paper, to introduce a degree of microporosity into otherwise macroporous materials. Our results also suggest the possibility of modular 'mix and match' strategies in which a number of different molecular pores are combined in a single-amorphous solid, each perhaps containing a different chemical functionality 39 , without satisfying the stringent requirements of co-crystallization 40 .…”
Section: Discussionmentioning
confidence: 88%
“…We found that the formation of nal products, H 2 O and N 2 , as shown in Fig. 7, begins shortly aer the initial dissociation of NO 2 , with the population of these nal products at 100 ps increasing dramatically with temperature, thereby increasing the energy release. These nal products in CL-20 appear earlier than in the cocrystal.…”
mentioning
confidence: 74%
“…Given the extensive debate on how to deal with the term 'cocrystal', be it from a chemical or a legal perspective (Stahly, 2009;Childs & Zaworotko, 2009;Desiraju, 2003;Dunitz, 2003), it is probably an act of folly to include the term in the title of any manuscript, let alone in one that aims to briefly address the possible impact that co-crystals and co-crystallizations may have on fundamental and applied chemistry.…”
Section: Introductionmentioning
confidence: 99%